HUBUNGAN TINGKAT KECERDASAN SPIRITUAL DENGAN KESADARAN SANTRI DALAM MENJALANKAN PERATURAN PONDOK - Muhammad Kusni Mubarok; Waslah - (JoEMS (Journal of Education and Management Studies), 2020)
This research is motivated by the spiritual intelligence of the students in terms of people who have a good personality, it is supported by the boarding school environment. In the boarding school students will get used to good education, such as discipline, craft, courtesy, hospitality and many other good qualities. But the awareness of students is not fully reflected in the students of Al Muhajirin 3. Most of them are less concerned about the cleanliness of the environment of the cottage, most students still pay less attention to speech when communicating with fellow students. The purpose of this study was to determine the level of spiritual intelligence and awareness of students in implementing the rules in Al Muhahirin 3 Islamic boarding school, as well as to analyze the presence or absence of the influence of the level of spiritual intelligence and awareness of students in the Islamic boarding school. This research approach uses a quantitative approach. Data collection uses questionnaires, interviews, observations, and documentation. The research data were analyzed with product moment correlation to get the results of the hypotheses that have been set. Research shows that Santri's Spiritual Intelligence is very high criteria, students' awareness in carrying out the rules obtained by high criteria, and r count with an amount of 0.803 is greater than rtable, so Ha is accepted ie "there is a relationship between the level of spiritual intelligence with the awareness of students in carrying out the rules of Islamic Boarding School Al Muhajirin 3 Bahrul 'Ulum Tambakberas Jombang.